1991
DOI: 10.1111/j.1365-2133.1991.tb06030.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro DNA synthesis of keratinocytes in normal human skin, psoriasis, seborrhoeic keratosis, Bowen's disease and basal cell carcinoma

Abstract: The DNA-synthesizing cells in benign and malignant keratotic diseases including psoriasis, seborrhoeic keratosis, Bowen's disease and basal cell carcinoma were studied. Cells in S-phase were labelled after small pieces of the lesions were incubated in tissue culture medium that contained 5-bromo-2'-deoxyuridine (BrdU). The labelling of DNA was analysed using the labelling index and pattern. Although the malignant diseases tended to show a higher DNA labelling index, neither this nor the loss of polarity alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
2
9
2
Order By: Relevance
“…This hypothesis is reinforced by the observation of a higher frequency of Ki67-positive cells in NSRE than in normal epidermis. Other groups using different culture systems have reported similar results [14,37,401 when epidermis reconstructed from normal dissociated keratinocytes developed other psoriatic features including the expression of Psi3 antigen [35] and the production of interleukin 6 [22].…”
Section: Discussionsupporting
confidence: 56%
“…This hypothesis is reinforced by the observation of a higher frequency of Ki67-positive cells in NSRE than in normal epidermis. Other groups using different culture systems have reported similar results [14,37,401 when epidermis reconstructed from normal dissociated keratinocytes developed other psoriatic features including the expression of Psi3 antigen [35] and the production of interleukin 6 [22].…”
Section: Discussionsupporting
confidence: 56%
“…The present data showed that a few secretory cells were in S-phase in both eccrine and apocrine sweat glands; therefore, these cells could proliferate. The labeling index of BrdUrd in eccrine secretory cells was much lower than that in normal epidermis (0.09-0.14% vs 1.4 0.4%) (6). Nevertheless, we believe that the presence of proliferating cells was valid, since both the BrdUrd and the PCNA that it is unlikely that myoepithelial cells proliferate and replace lost secretory cells, a t least in normal sweat glands.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, small pieces of skin were incubated in a medium containing 100 pM BrdUrd under 3 atmospheric pressures of 95% 02-5% CO2 as reported by Sasaki and colleagues (11,12). The validity and usefulness of this method have been reported in previous publications, including our own (6,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, the onset of terminal differentiation is precocious as shown by involucrin expression, 9,10 although dysplasia is not a feature. The proliferative fraction is similarly increased in in-situ and invasive neoplasia, 11,12 while abnormal differentiation is seen as a feature of dysplasia by conventional light microscopy. These observations suggest that proliferation and differentiation are uncoupled in many skin disorders, both benign and malignant.…”
mentioning
confidence: 93%